Genome size of alpine plants does not predict temperature resistance - Sklenář, Petr; Ptáček, Jan; Klimeš, Adam (Planta, 2022)
Genome size of alpine plants is not related to their resistance against frost and heat. Genome size is a variable trait in angiosperms, and it was suggested that large genome size represents a constraint in stressful environments. We measured genome size and resistance to frost and heat in 89 species of plants from tropical and temperate alpine habitats. Genome size of the species, ranging from 0.49 pg to 25.8 pg across the entire dataset, was not related to either frost or heat resistance in either group of plants. Genome size does not predict resistance to extreme temperatures in alpine plants and is thus not likely to predict plant responses to climate changes.
Keywords: Seasons; rostliny; Functional traits; Freezing resistance; Genome Size; Climate Change; Temperature; Tropical and temperate mountains; roční období; délka genomu; klimatické změny; Heat resistance; Plants; teplota; Cellular DNA content